Long-Term Stability of Blood Serum Biomarkers in Traumatic Brain Injury: A Feasibility Study - van der Horn, Harm Jan; Visser, Koen; Bijzet, Johan; Vos, Pieter; van der Naalt, Joukje; Jacobs, Bram (Frontiers in Neurology, 2022)
Few studies on traumatic brain injury (TBI) have investigated the stability of blood serum biomarkers after long-term storage at low temperatures. In the current feasibility study we analyzed acute phase serum samples from patients with mild TBI as well as patients with moderate and severe TBI that were collected more than ten years ago (old samples). We were particularly interested in mild TBI, because injury effects are more subtle in this category as compared to moderate-severe TBI. Therefore, the primary objective was to find out whether several biomarkers were still be detectable for these patients. Additionally, we examined whether biomarker levels varied as a function of injury severity. For comparison, we also analyzed samples from an ongoing mTBI cohort (new samples) and healthy controls. Samples were treated with care and were not being subjected to freeze-thaw cycles. We measured concentrations of interleukins (IL6 and 10) and brain specific markers (total tau, UCH-L1, GFAP and NF-L). No significant differences in biomarker concentrations were found between old and new mild TBI samples. For IL6, IL10 and UCH-L1 higher concentrations were found in moderate and severe TBI as compared to mild TBI. In conclusion, our study shows that long-term storage does not rule out the detection of meaningful biomarker concentrations in patients with TBI, although further research by other laboratories is warranted.